Assessment of unterraced and terraced farming system on livestock development in mid-hills of Nepal - Giri, Gopal; Nepali, Dainik B; Shrestha, Bhola S (Journal of Agriculture and Environment, 2014)
The unterraced farming (Pata) system which is being practiced in few districts of mid hills of Nepal was assessed in terms of livestock holding and livestock feed availability against the terraced farming system. Field study and household survey was conducted in Arghakhanchi (representing unterraced/Pata) and Tanahun (representing terraced) farming system by selecting 90 households (HHs) from each districts randomly. The study showed that there was only 1.89 Livestock Unit (LU)/HH in Arghakhanchi as compared to 2.64 LU/HH in Tanahun (p